Pengaruh Kombinasi Proses Pretreatment (Koagulasi-Flokulasi) Dan Membran Reverse Osmosis Untuk Pengolahan Air Payau - Sastra Silvester Ginting; Jhon Armedi Pinem; Rozanna Sri Irianty (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2016)
In general, Riau coastal communities difficult to get clean water because the water resources in the coastal areas of brackish water is not to be used for everyday life. Therefore, the necessary technology for processing brackish water into clean water. This research aims to determine the performance of the process of coagulation-flocculation and reverse osmosis membrane on processing brackish water into clean water. Reverse osmosis membrane used is a type of spiral wound measuring 0,0001 μm and coagulant used PAC coagulant. In this study, the variable used is the concentration of PAC coagulant and reverse osmosis membrane operating pressure. Experiment result obtained the optimum condition of PAC coagulant concentration is 150 mg/L, which PAC can be designated turbidity up to 88.46% and 91.84% hardness. At a pressure of 8 bar, permeate flux preceded by coagulation-flocculation of 25.81 L/m2.jam. Rejection coefficient at a pressure of 8 bar brackish water after coagulation-flocculation had 98.72% of TDS; 96.99% of turbidity; 97.62% of organic substances; 96.37% of hardness and 92.4% chloride.Keywords: brackish water, coagulation-flocculation, reverse osmosis membranes.